Knowledge, Attitude and Practice towards Novel Corona virus (COVID-19): A Cross-Sectional Study among Social Media Users in Nepal - Neupane, Umesh; Joshi, Dirgha Raj; Joshi, Puspa Raj; Chaudhary, Sanjay; Chaurasia, Lokeshwar; Sha, Laxmi; Giri, Shree Shyam (Janaki Medical College Journal of Medical Science, 2020)
Background and Objectives: Public adherence to preventive measures like social distancing, lockdown, improved hygiene is influenced by their knowledge and attitude toward COVID-19. The effectiveness of those mitigation measures is highly dependent on the cooperation and compliance of all residents of the country. This study aims to assess the knowledge, attitude and practice of social media users with respect to six variables of socio-demographic parameters regarding the corona virus disease . Material and methods: The cross-sectional study design was employed through an online survey. The data were collected from 218 respondents from April 15 to June 7, 2020 through Google Form. Frequency, percentage, Mann-Whitney U and Kruskal Wallis H Test were used to analyze the data. Results: A high level of sensible knowledge regarding the overall knowledge (Mean=0.73, SD=0.11) about COVID-19 was observed. Participants have shown good sense of knowledge towards awareness (Mean=0.73, SD=0.14) and prevention (Mean=0.88, SD=0.15) based knowledge as compared to the symptom (Mean=0.49, SD=0.19) based knowledge. In response to attitude and practice, seven out of ten participants (70.6%) believed that the country will succeed in controlling the virus. A good number of participants were wearing face masks (94.5%), improving hygiene (92.7%) and using sanitizer/soap (94%). Around 91.7% of them were maintaining social distancing whereas 73.9%of participants think that the ongoing lockdown should be extended to control the transmission of virus. More dangerously, 42.7 % of participants believed anti-malarial drugs are useful for treating the patients with COVID-19. Conclusion: The present study revealed a good knowledge, optimistic attitude and appropriate practice among social media users towards COVID-19. The findings of this study might serve as the baseline for planning awareness campaigns to improve the knowledge, attitude and practice in some critical aspects to control the virus in public level, and implementing government efforts and plan for better containment of COVID-19.